EP1273 Fertility preservation in malignant ovarian tumors: experience of the French ESGO labeled -ovarian tumours center and pregnancy associated cancer network (CALG) national expert center at Tenon University Hospital. (1st November 2019) - Lier, A; Geoffron, S; Prades, M; Sermondade, N; Kolanska, K; Varinot, J; Wafo, E; Uzan, C; Daraï, E; Bendifallah, S; Chabbert-Buffet, N
Abstract : Introduction/Background: Progress in early diagnosis, treatment efficacy have allowed increased life expectancy in cancer patients (1). Therefore, approximately 6% childbearing age individuals are cancer survivors (2). In this specific setting, 20% of malignant epithelial ovarian tumours (MEOT) are diagnosed before the age of 44, with a 91.2% five years survival rate for stage IA and IB (3). Similarly rare malignant ovarian tumors (RMOT) and borderline ovarian tumours (BOT) more frequently occur in women of childbearing age (4). Personalized counseling on post treatment ovarian function and possibilities of fertility preservation (FP) are part of oncological patients' care (5). However the safety and efficiency evidence level is currently too limited to allow specific recommendations. Therefore, we report the experience in FP for patients with malignant ovarian tumours, at a French ESGO labeled national expert center and pregnancy-associated cancer network (CALG). Methodology: Data from 43 patients with malignant ovarian tumors who underwent a FP between February 2013 and July 2019 were analysed from the prospective unicentric database. Results: Pathological diagnosis was 5 (11.6%) MEOT, 14 (32.6%) RMOT, 24 (55.8%) BOT, mostly unilateral (76.5%) and stage I (87.9%). Mean age at diagnosis and tumor size was 26.8 and 97.4 mm respectively. Before fertility preservation, mean antral follicle count and AMH levels were 9 [0–20], and 2.26 ng/ml [0.1–10]. Mean age at fertility preservation was 29.2 [17.4–37.1]. Six ovarian tissue freezing procedures were performed out of 14 proposed. 23 oocyte freezing procedures were performed after tumor surgical treatment out of 26 proposed, with a median delay of 188 days. The mean mature oocytes collected number was 12.9. No FP was proposed for 5 patients. Conclusion: Oocyte and ovarian tissue cryopreservation can be offered to patients with malignant ovarian tumor. More data are needed to confirm ovarian stimulation and ovarian tissue grafting safety. Disclosure: Nothing to disclose